Current legal issues concerning awqéf in Malaysia - Syed Abdul Kader , Sharifah Zubaidah; Md Dahlan, Nuarrual Hilal (Institute of Objective Studies, 2013)
Waqf falls under the jurisdiction of the Syariah Court according to List II of the Ninth Schedule to the Federal Constitution. This is further entrenched in the Administration of Islamic Law Enactments of the respective states in Malaysia. Nevertheless, from judicial decisions, ‘waqf’ is still, until today, being determined by the civil courts. In some judicial decisions, waqf issues have been marginalized by the civil courts as they are considered side issues. In consequence, the persons having interest in waqf under Islamic law are deprived of their rights. This paper will elaborate on the series of decided cases involving waqf in Malaysia, examine the issues raised, and will also analyze the judicial decisions made. Such analysis will assist in formulating a future framework for the management and development of waqf lands in Malaysia.